2021
DOI: 10.3390/w13212949
|View full text |Cite
|
Sign up to set email alerts
|

Host Dependence of Zooplankton-Associated Microbes and Their Ecological Implications in Freshwater Lakes

Abstract: Zooplankton is colonized by quite different microbes compared with free-living and particle-associated bacteria, serving as a non-negligible niche of bacteria in aquatic ecosystems. Yet detailed analysis of these bacterial groups is still less known, especially in freshwater lakes. To widen our knowledge of host-microbe interaction and bacterial ecosystem functions, we chose two specific populations of zooplankton, i.e., cladoceran Moina and copepod Calanoids, as hosts from five natural lakes, and illustrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…In the symbiosis between plankton and microorganisms, plankton provides necessary nutrients and space for microorganisms and affects their metabolic capacity, thus affecting the cycling of carbon and nitrogen in the lake (Siegert et al 2001). DOM can also be decomposed by microorganisms in the absence of light as proved in a previous study (Wang et al 2021). Considering the effect of light reduction on the decomposition of DOM during freezing periods, it was predicted that the loss of DOM in the water samples caused by microbial and photolytic action in the melting process was 3.9%-11.9%.…”
Section: Effects Of Lake Microorganisms On Dom Components During Free...mentioning
confidence: 65%
“…In the symbiosis between plankton and microorganisms, plankton provides necessary nutrients and space for microorganisms and affects their metabolic capacity, thus affecting the cycling of carbon and nitrogen in the lake (Siegert et al 2001). DOM can also be decomposed by microorganisms in the absence of light as proved in a previous study (Wang et al 2021). Considering the effect of light reduction on the decomposition of DOM during freezing periods, it was predicted that the loss of DOM in the water samples caused by microbial and photolytic action in the melting process was 3.9%-11.9%.…”
Section: Effects Of Lake Microorganisms On Dom Components During Free...mentioning
confidence: 65%
“…Studies have shown that Alphaproteobacteria is not only dominant in rotifer-associated bacteria, but also widely exists in Cladocera ( Grossart et al, 2009 ), Copepods ( Dziallas et al, 2013 ) and Protozoa ( Khalzov et al, 2021 ). The members of Rhizobiales are mostly nitrogen-fixing bacteria, which are the most common plant symbioses and also play a potential role in the carbon cycle of freshwater lakes ( Erlacher et al, 2015 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The microbiota associated with Daphnia consists of β-Proteobacteria, γ-Proteobacteria, and Flavobacteria (Cooper and Cressler, 2020). However, individual zooplankton species can vary in their ability to host bacterial communities (Wang et al, 2021).…”
Section: Zooplankton-bacterial Microbiotic Particlesmentioning
confidence: 99%